Dual-Electrode In Situ Infrared Spectroscopy for Fuel Cells. Issue 4 (1st January 2016) - Sorte, Eric G.; Chen, De-Jun; Tong, YuYe J.
Abstract : We have designed and built a rotating dual-electrode infrared cell for in situ electrochemical (EC) attenuated-total-reflection infrared spectroscopic (ATR-IRS) investigations of fuel cells and batteries under operating conditions. Our design is unique in that it for the first time allows for ATR-IRS measurements to be made on both anode and cathode while a fuel cell is operational and electrochemical measurements are on-going. We demonstrate the device's capabilities by making sequential, iterative ATR-IRS measurements of direct methanol fuel cell (DMFC) reactions at the PtRu anode and Pt cathode as a function of cell driving current (thus potential) while controlling the electrochemical parameters. Different chemical species involved in the anodic methanol oxidation reaction (MOR) versus those involved in the cathodic oxygen reduction reaction (ORR) can be identified and quantified during the operation of the fuel cell. The same setup can be applied directly to study anodic and cathodic chemistry in batteries.